Use of multiparametric magnetic resonance imaging in prostate cancer active surveillance - Glass, Allison S.; Dall'Era, Marc A. (BJU international, 2019)
Objectives To review the role of multiparametric magnetic resonance imaging (mpMRI) for active surveillance (AS) of prostate cancer. Materials and Methods We performed a comprehensive search of Medline and Embase databases for relevant articles in the English language. Search terms included ‘prostate cancer', ‘active surveillance' or ‘monitoring', ‘expectant management', and ‘MRI'. We also reviewed practice guidelines from recognized international associations or societies involved in prostate cancer care. Articles were selected by both authors for relevance to the subject matter. Results The ability of mpMRI to visualize primarily high‐grade tumours within the prostate may improve risk stratification for men considering AS for prostate cancer. Multiple mostly single‐institution studies have found that the addition of mpMRI and a targeted biopsy strategy can improve AS patient selection over standard TRUS biopsy alone. The high negative predictive value of mpMRI may allow men to avoid early repeat biopsy and may offer the possibility to tailor biopsy strategies. The presence of a radiographically positive lesion on mpMRI at baseline is predictive of higher likelihood of radiographic progression over time while on AS. Conclusions MRI has shown promise in both patient selection and monitoring for men who undergo AS for prostate cancer. There are multiple barriers to the widespread use of mpMRI for AS including quality, cost and access to care.